Morphological considerations concerning the nationalisation of medical terms - Høy, Asta (HERMES - Journal of Language and Communication in Business, 2000)
The Danish medical terminology, part of which used to be in pure Latin and Greek, is characterized by an increasing degree of nationalisation, due mainly to the decreasing knowledge of the classical languages. At the same time, the terminology is influenced by English, this century’s medical lingua franca. The present situation calls for an overall language policy including both the status and the corpus of the language for medical purposes. Hopefully, the future Danish Medical Language Advisory Board, which has been in the melting pot for a couple of years, will be able to act as a decision-and consensus-maker concerning these questions. In this article, the types of mor-phemes involved in the construction of the so-called neo-classical compounds are considered. Indeed, it may be assumed that a clear view of the morphological charac-teristics of the Danified neo-classical terms, the hybrids, could be a help in connection with setting up some general guidelines for their construction and spelling which might eliminate the confusion now prevailing in the area.